AMPKα1: A glucose sensor that controls CD8 T‐cell memory. Issue 4 (13th February 2013) - Rolf, Julia; Zarrouk, Marouan; Finlay, David K.; Foretz, Marc; Viollet, Benoit; Cantrell, Doreen A.
<x xml:space="preserve">Abstract</x> The adenosine monophosphate‐activated protein kinase (AMPK) is activated by antigen receptor signals and energy stress in T cells. In many cell types, AMPK can maintain energy homeostasis and can enforce quiescence to limit energy demands. We consequently evaluated the importance of AMPK for controlling the transition of metabolically active effector CD8 T lymphocytes to the metabolically quiescent catabolic memory T cells during the contraction phase of the immune response. We show that AMPKα1 activates rapidly in response to the metabolic stress caused by glucose deprivation of CD8 cytotoxic T lymphocytes (CTLs). Moreover, AMPKα1 restrains mammalian target of rapamycin complex 1 activity under conditions of glucose stress. AMPKα1 activity is dispensable for proliferation and differentiation of CTLs. However, AMPKα1 is required for in vivo survival of CTLs following withdrawal of immune stimulation. AMPKα1null T cells also show a striking defect in their ability to generate memory CD8 T‐cell responses during Listeria monocytogenes infection. These results show that AMPKα1 monitors energy stress in CTLs and controls CD8 T‐cell memory.